MEDIA TRUST AND MISINFORMATION - Gore, Rupali Prakash; Shelke, Rekha (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Media trust and misinformation reveal a nuanced, multifaceted relationship shaped by the dynamics of digital communication, psychological factors, and intervention strategies. Media trust explores various dimensions including the impact of perceived journalistic quality, political ideology, measurement scales, cross-cultural comparisons, and media's psychological effects. Media trust and misinformation are intricately linked phenomena that significantly influence public perception, information consumption, and societal responses, particularly in crisis contexts. Recent research highlights several critical dimensions in understanding how media trust is affected by misinformation, how misinformation spreads, and the implications for public behavior and institutional credibility. Perceptions of misinformation and disinformation in the news media environment are closely associated with declining trust in traditional news sources. A large-scale survey across 10 European countries revealed that individuals who perceive high levels of misinformation and disinformation tend to show reduced trust in mainstream news media outlets, particularly traditional television news. Correspondingly, these individuals decrease their consumption of TV news but do not exhibit significant changes in newspaper or mainstream online news usage. Importantly, those with stronger beliefs about misinformation and disinformation are more inclined to consume news from social media platforms and alternative outlets characterized by anti-establishment perspectives. This shift suggests a reinforcement of echo chambers and selective exposure, where distrust in credible sources leads audiences toward less vetted or ideologically aligned content sources, potentially exacerbating misinformation exposure.